2009 IEEE International Symposium on Information Theory 2009
DOI: 10.1109/isit.2009.5205970
|View full text |Cite
|
Sign up to set email alerts
|

A new sum-rate outer bound for Gaussian Interference Channels with Generalized Feedback

Abstract: Interference Channels (IFC) with Generalized Feedback (GF) model wireless channels where every node overhears the transmission of other nodes and uses it to engage in cooperative communication strategies. The overheard signals, instead of being treated as interference, furnish the basis for cooperation among otherwise uncoordinated users. Although cooperative communications is not equivalent to virtual Multi-Input-MultiOutput (MIMO) communications, it has been shown to benefit the rate performance of all the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…For the situation in which both transmitters observe noisy feedback from both receivers, it was shown that feedback looses its value when the noise in the feedback signal is of the same variance as the noise in the direct link. Finally, note that generalized feedback (or, equivalently source cooperation), studied in [27], [56], and [57] can also be considered rate-limited feedback when the SNR is finite. In [56] and [57], outer bounds were derived for ICs with generalized feedback.…”
Section: Introductionmentioning
confidence: 99%
“…For the situation in which both transmitters observe noisy feedback from both receivers, it was shown that feedback looses its value when the noise in the feedback signal is of the same variance as the noise in the direct link. Finally, note that generalized feedback (or, equivalently source cooperation), studied in [27], [56], and [57] can also be considered rate-limited feedback when the SNR is finite. In [56] and [57], outer bounds were derived for ICs with generalized feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Our derivation here shows they hold for any IFC-GF. 4) Another generalization of [15,Th.1] for Gaussian channels in strong interference can be found in [17], where we showed that the capacity region of a Gaussian IFC-GF cannot depend on the channel coefficients h 11 and h 22 . For the Gaussian case with strong interference, we gave a receiver the GF signal of its transmitter as side information so that both messages could be decoded.…”
Section: Theorem Ii2 If the Channel Is Semi-deterministic As Inmentioning
confidence: 79%
“…We would also like to remark that the work on generalized feedback in [14][15][16][17], as well as the work on source cooperation by two sources overhearing each other's messages over a noisy channel in [24] are closely related to our work. The outer and inner bounds derived in [14,16] and [24], concurrent to our work in [1,2], can be particularized to obtain the sum-capacity result shown in Lemma 4.4.…”
Section: Introductionmentioning
confidence: 86%
“…Next, we present an outer-bound on the sum-capacity of the feedback model (1111) we derived in [1]. Concurrent to [1], the authors in [15] derive an outer-bound for the generalized feedback model. The authors in [24] also derive outer bounds for interference channels with source cooperation, which can be particularized for the linear symmetric deterministic interference channel to obtain the same result.…”
Section: A Outer Boundsmentioning
confidence: 99%
See 1 more Smart Citation